Bone Deterioration in Response to Chronic High‐Altitude Hypoxia Is Attenuated by a Pulsed Electromagnetic Field Via the Primary Cilium/HIF‐1α Axis. (13th February 2023) - Hao, Xiaoxia; Wang, Dan; Yan, Zedong; Ding, Yuanjun; Zhang, Juan; Liu, Juan; Shao, Xi; Liu, Xiyu; Wang, Lu; Luo, Erping; Cai, Jing; Jing, Da
ABSTRACT: Chronic high‐altitude hypoxia induces irreversible abnormalities in various organisms. Emerging evidence indicates that hypobaric hypoxia markedly suppresses bone mass and bone strength. However, few effective means have been identified to prevent such bone deficits. Here, we assessed the potential of pulsed electromagnetic fields (PEMFs) to noninvasively resist bone deterioration induced by hypobaric hypoxia. We observed that exogenous PEMF treatment at 15 Hz and 20 Gauss (Gs) improved the cancellous and cortical bone mass, bone microstructure, and skeletal mechano‐properties in rats subjected to chronic exposure of hypobaric hypoxia simulating an altitude of 4500 m for 6 weeks by primarily modulating osteoblasts and osteoblast‐mediated bone‐forming activity. Moreover, our results showed that whereas PEMF stimulated the functional activity of primary osteoblasts in hypoxic culture in vitro, it had negligible effects on osteoclasts and osteocytes exposed to hypoxia. Mechanistically, the primary cilium was found to function as the major electromagnetic sensor in osteoblasts exposed to hypoxia. The polycystins PC‐1/PC‐2 complex was identified as the primary calcium channel in the primary cilium of hypoxia‐exposed osteoblastic cells responsible for the detection of external PEMF signals, and thereby translated these biophysical signals into intracellular biochemical events involving significant increase in the intracellular soluble adenylyl cyclase (sAC) expression and subsequent elevation of cyclic adenosine monophosphate (cAMP) concentration. The second messenger cAMP inhibited the transcription of oxygen homeostasis‐related hypoxia‐inducible factor 1‐alpha (HIF‐1α), and thus enhanced osteoblast differentiation and improved bone phenotype. Overall, the present study not only advances our understanding of bone physiology at high altitudes, but more importantly, proposes effective means to ameliorate high altitude‐induced bone loss in a noninvasive and cost‐effective manner. © 2023 American Society for Bone and Mineral Research (ASBMR). Abstract : Schematic diagram showing the mechanism whereby PEMF treatment counteracts bone loss resulting from chronic hypobaric hypoxia.